2022
DOI: 10.1017/ice.2022.7
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-resistant Enterococcus sequence type 1478 spread across hospitals participating in the Canadian Nosocomial Infection Surveillance Program from 2013 to 2018

Abstract: Objective: To analyze the spread of a novel sequence type (ST1478) of vancomycin-resistant Enterococcus faecium across Canadian hospitals. Design: Retrospective chart review of patients identified as having ST1478 VRE bloodstream infection. Setting: Canadian hospitals that participate in the Canadian Nosocomial Infection Surveillance Program (CNISP). Methods: From 2013 to 2018, VRE bloodstream isolates collected from participating CNISP hospitals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Previously, VVE strains lacking the pstS gene have been identified only in the ST1421 clone [ 6 , 10 , 16 ]. To date, VRE ST1478 was only detected across Canadian hospitals by national surveillance [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, VVE strains lacking the pstS gene have been identified only in the ST1421 clone [ 6 , 10 , 16 ]. To date, VRE ST1478 was only detected across Canadian hospitals by national surveillance [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…These pstS -null sequence types (e.g., ST1421 and ST1424) have been reported in Australia, Denmark, Scotland, and South Korea [ 16 , 21 23 ]. Very recently, a novel pstS -null ST1478 was also disseminated across acute care hospitals in Canada [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…bone marrow transplants, solid organ transplants, cancer patients, etc.) (( 41 )). Although there is a lack of recent data on VRE BSI rates in comparable jurisdictions, there have been increasing trends noted in Europe (( 42 – 45 )), which may be associated, in part, with the introduction and spread of a new clone and gaps in infection prevention practises (( 44 46 )).…”
Section: Discussionmentioning
confidence: 99%
“…We did however note differences in the percentage of isolates residing within putative transmission clusters among different lineages, with lineage ST1478 showing a significantly higher proportion of clustered isolates. Prior literature has found that the ST117 lineage was responsible for numerous VREfm hospital outbreaks 12,14,33 ; however, the ST1478 lineage has only been detected in the US and Canada 19 . Taken together, these findings suggest that some VREfm lineages might be more efficient than others at transmitting between patients in the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…CC17 strains frequently encode antimicrobial resistance genes, mobile genetic elements, and genes that enable the metabolism of amino sugars found on GI epithelia and mucin, likely contributing to the success of CC17 strains in healthcare settings [12][13][14][15][16][17][18] . This success is exemplified by CC17 lineages being identified as responsible for widespread outbreaks and increased rates of invasive infection 14,15,17,19 . Although several prior studies have investigated VREfm population structure and dynamics within healthcare settings, we know little about the factors that drive the emergence and persistence of particular VREfm lineages in the hospital.…”
Section: Introductionmentioning
confidence: 99%